The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/s004420050029
|View full text |Cite
|
Sign up to set email alerts
|

The impact of phosphorus on interactions of the hemiparasitic angiosperm Rhinanthus minor and its host Lolium perenne

Abstract: The effects of phosphorus supply on the outcome of interactions between the hemiparasitic angiosperm Rhinanthus minor L. with its host species Lolium perenne L. were investigated in a glasshouse experiment. Host plants were grown in 3-l pots in the presence and absence of R. minor at limiting (0.13 mM P) and optimal (0.65 mM P) concentrations of phosphorus for the growth of the host species. Phosphorus was supplied at 2-day intervals in the form of half-strength Long Ashton nitrate-based solution with phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 30 publications
3
36
2
Order By: Relevance
“…2). Similar results were also declared by some other researchers (Glatzel 1983;Davies & Graves 2000;Hosseini et al, 2008;Glatzel & Geils 2009). The reason of high P concentration in mistletoe leaves is possibly due to the absence of a phloem connection between host and hemi-parasite, high transpiration rates and the lack of a retranslocation system (Smith & Stewart 1990;Glatzel & Geils 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2). Similar results were also declared by some other researchers (Glatzel 1983;Davies & Graves 2000;Hosseini et al, 2008;Glatzel & Geils 2009). The reason of high P concentration in mistletoe leaves is possibly due to the absence of a phloem connection between host and hemi-parasite, high transpiration rates and the lack of a retranslocation system (Smith & Stewart 1990;Glatzel & Geils 2009).…”
Section: Discussionsupporting
confidence: 90%
“…The reason of high P concentration in mistletoe leaves is possibly due to the absence of a phloem connection between host and hemi-parasite, high transpiration rates and the lack of a retranslocation system (Smith & Stewart 1990;Glatzel & Geils 2009). Davies and Graves (2000) reported that increasing P amount in host tissues had a positive effect on the host, with the negative impact of parasitism being greatly reduced at the higher P level.…”
Section: Discussionmentioning
confidence: 99%
“…Bardgett et al (2006) found no interactions between R. minor and soil fertility or manure application on aboveground biomass in a mesocosm experiment, but R. minor increased species diversity in lownutrient soil. The results of two-pot culture experiments suggest that the eVect of a parasite was greater in nutrientpoor soils (Matthies and Egli 1999;Davies and Graves 2000), although the latter study did not report results for the interaction, while Cameron et al (2005) showed that R. minor had a larger eVect on competitive abilities of the grass Poa pratensis under high-nutrient levels. Together, these studies, and those of Cameron et al (2009), suggest that eVects of hemiparasites on communities are not straight-forward responses to resource supply in many systems.…”
Section: (B)mentioning
confidence: 80%
“…Bullock and Pywell (2005) suggested that the effect could be determined by the position of the plot on a productivity gradient with respect to the hump-back model of dependence of species richness on productivity (Grime 1979). Indeed, the effect of hemiparasites on a plant community could be affected by the nutrient status of the environment: the effect of a hemiparasite on hosts (e.g., biomass reduction) decreases with increasing amounts of nutrients in the soil (Gibson and Watkinson 1991;Matthies and Egli 1999;Davies and Graves 2000). Biomass allocation into their own root system is usually very low in hemiparasites (Matthies 1995b(Matthies , 1997(Matthies , 1998 and root hemiparasitism enables them to acquire nutrients with limited investment into the root system.…”
Section: Introductionmentioning
confidence: 98%
“…Accordingly, R. minor is associated with meadows of relatively low productivity and intensive fertilization can result in its extinction (Matthies 1995a). A considerable part of this evidence comes from pot experiments (Gibson and Watkinson 1991;Matthies and Egli 1999;Davies and Graves 2000).…”
Section: Introductionmentioning
confidence: 99%